PKM Usaha Ilabulo Bakar Kecamatan Kota Selatan Provinsi Gorontalo - Rizal, Rahma; Annur, Haditsah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
The partner in the community partnership program is Usaha Ilabulo Bakar. Ilabulo is a typical snack from Gorontalo. Formerly by the kings, Ilabulo symbolizes